Interleukin-26–DNA complexes promote inflammation and dermal-epidermal separation in a modified human cryosection model of bullous pemphigoid - Mizuno, Yuka; Shibata, Sayaka; Ito, Yukiko; Taira, Haruka; Sugimoto, Eiki; Awaji, Kentaro; Sato, Shinichi (Frontiers in Immunology, 2022)
Bullous pemphigoid (BP) is an autoimmune disease characterized by autoantibody-mediated activation of immune cells and subepidermal blister formation. Excess amounts of extracellular DNA are produced in BP, however, it remains unclear how extracellular DNA contribute to BP pathogenesis. Here we show a possible mechanism by which interleukin (IL)-26 binds to extracellular DNA released from neutrophils and eosinophils to support DNA sensing. Patients with BP exhibited high circulation levels of IL-26, forming IL-26–DNA complexes in the upper dermis and inside the blisters. IL-26–DNA complexes played a dual role in regulating local immunity and blister formation. First, they enhanced the production of inflammatory cytokines in monocytes and neutrophils. Second, and importantly, the complexes augmented the production and activity of proteases from co-cultured monocytes and neutrophils, which induced BP180 cleavage in keratinocytes and dermal-epidermal separation in a modified human cryosection model. Collectively, we propose a model in which IL-26 and extracellular DNA synergistically act on immune cells to enhance autoantibody-driven local immune responses and protease-mediated fragility of dermal-epidermal junction in BP.